LAJU PERTUMBUHAN POPULASI Brachionus plicatilis O. F. Muller DENGAN PEMBERIAN KOTORAN AYAM KAMPUNG (Gallus varius L.) DAN AYAM BROILER (Gallus demostica L.) PADA MEDIA KOMBINASI PUPUK UREA DAN TSP - Surya Darmawansyah; Arlen Hanel John; Mayang Sari Yeanny (Saintia Biologi, 2013)
The relationship between growth rate of Brachionus plicatilis O. F. Muller population and feeding that contain addition of local chicken manure (Gallus varius L.) and broiler chicken’s (Gallus domestica L.) in urea and triple superphosphat (TSP) was conducted on September 2012 in Animal Systematic Laboratory, Biology Department, Mathematics and Sains Faculty, Sumatera Utara University. This research used complete randomized design (CRD) with 4 treatments chicken manure, that is M1 (300 mg/2 L local), M2 (400 mg/2 L local), M3 (300 mg/2 L broiler) and M4 (400/2 L broiler), with 6 times repeated and 8 times observation during 16 days. The result showed that the growth rate of B. plicatilis the highest on medium M4 is 8.492 indx2x10-3xday-1 and have the lowest on the medium M1 is 8.386 indx2x10-3xday-1. These showed that using broiler chicken’s manure is better than local chicken’s manure. Keywords : Brachionus plicatilis, growth rate, broiler chicken manure, local chicken manure